If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 = 4a + -1a Combine like terms: 4a + -1a = 3a -3 = 3a Solving -3 = 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. -3 + -3a = 3a + -3a Combine like terms: 3a + -3a = 0 -3 + -3a = 0 Add '3' to each side of the equation. -3 + 3 + -3a = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -3a = 0 + 3 -3a = 0 + 3 Combine like terms: 0 + 3 = 3 -3a = 3 Divide each side by '-3'. a = -1 Simplifying a = -1
| 2(x+5)=-x+2(x^2-5) | | 3y+9=48 | | -5.49+0.78=3.98 | | 3a*a=3+12a | | 1+6x=-5x+122 | | 1/4(18-a)=9.5 | | n+23=-24 | | 3v-v=14 | | -6(8-2a)=-92 | | 8-4=-7 | | x=3x+2.2(10-x) | | C=48m+0.99n | | 1+1=4z-10 | | 4x+x=750 | | 4(x-3)=8(x+2) | | 29+2b=5(b+4) | | 14+(35+36)= | | 6v-v=10 | | -40=32y-48 | | 8.164=2*3.14r | | 6x=2.2 | | 4(5c-1)-2=18c+6 | | 1=2a+b | | 2xy-y=10 | | C=24 | | 1/14(a-4)=2/7(a+6)-1/7a | | -24=-8x+48 | | 0=112-3x+2 | | 3y+2(y+1)=4 | | 5xy=5x+5y | | 52=x-7x-2 | | 7-10x=33-24x |